Endobronchial valves in treatment of persistent air leak: European case-series study and best practice recommendations : from an expert panel - Smesseim, Illaa; Morin-Thibault, Louis-Vincent; Herth, Felix; Tonkin, James; Shah, Pallav; Slebos, Dirk-Jan; Koster, David T.; Dickhoff, Chris; Daniels, Johannes Marlene Andreas; Annema, Jouke; Bonta, Peter (Respiration, 2024)
Introduction: Persistent air leak (PAL) is associated with prolonged hospitalization, high morbidity and increased treatment costs. Conservative treatment consists of observation, chest tube drainage, and pleurodesis. Guidelines recommend surgical evaluation if air leak does not respond after 3-5 days. One-way endobronchial valves (EBV) have been proposed as a treatment option for patients with PAL in which surgical treatment is not feasible, high risk or has failed. We aimed to provide a comprehensive overview of reported EBV use for PAL and issue best practice recommendations based on multicenter experience. Methods: We conducted a retrospective observational case-series study at four different European academic hospitals and provided best practice recommendations based on our experience. A systematic literature review was performed to summarize the current knowledge on EBV in PAL. Results: We enrolled 66 patients, male (66.7%), median age 59.5 years. The most common underlying lung disease was chronic obstructive pulmonary disease (39.4%) and lung cancer (33.3%). The median time between pneumothorax and valve placement was 24.5 days (interquartile range: 14.0-54.3). Air leak resolved in 40/66 patients (60.6%) within 30 days after EBV treatment. Concerning safety outcome, no procedure-related mortality was reported and complication rate was low (6.1%). Five patients (7.6%) died in the first 30 days after intervention. Conclusion: EBV placement is a treatment option in patients with PAL. In this multicenter case-series of high-risk patients not eligible for lung surgery, we show that EBV placement resulted in air leak resolution in 6 out of 10 patients with a low complication rate. Considering the minimally invasive nature of EBV to treat PAL as opposed to surgery, further research should investigate if EBV treatment should be expanded in low to intermediate risk PAL patients.
Online veröffentlicht: June 13 2024
Gesehen am 07.03.2025